Enhancing Disaster Nutrition Training in Surabaya, Indonesia: Aligning with Indonesia Ministry of Health's Healthcare Workforce Transformation Program - Rusyadi, Luthfi; Taufiqurrahman, Taufiqurrahman; Hafid, Fahmi; Soesanti, Inne; Shofiya, Dian; Hatijah, Nur; Pengge, Nuning Marina; Hindaryani, Nurul; Mujayanto, Mujayanto; Intiyati, Ani; Nugroho, Riezky Faisal; Latifolia, Ergia; Ratnasari, Devi Eka; Halimah, Husnul; Wardana, Endra Tri Kusuma; Prionggo, Anang; Putri, Intan Maulina Alifia; Sariman, Sarina (Media Publikasi Cendekia Indonesia, 2024)
The aim of this community service is to train the readiness of the community and academic community of Poltekkes Kemenkes Surabaya in facing disasters in Indonesia. The implementation method took place on May 6, 2024, at the Nutrition Department of Poltekkes Kemenkes Surabaya, involving 100 participants, including lecturers, students, and local residents. The training utilized interactive methods such as discussions, role play, and disaster simulations to enhance participants' understanding and engagement. The outcomes showed a significant improvement in disaster nutrition management skills in the Surabaya region. Participants not only gained theoretical knowledge of disaster nutrition but also practical skills applicable in real-life situations. Recommendations from this initiative include enhancing the provision of more in-depth training materials, using advanced technology for simulations, and improving logistical support for smoother implementation of future activities. This community service significantly contributes to enhancing the readiness of Poltekkes Kemenkes Surabaya and strengthening community resilience to disasters in Indonesia. For future community service activities, it is recommended to conduct more comprehensive implementations and involve a wider range of participants.